Regulatory function of DNA methylation mediated lncRNAs in gastric cancer - Nan Li; Anqi Zeng; Qian Wang; Maohua Chen; Shaomi Zhu; Linjiang Song (Cancer Cell International, 2022)
Abstract As one of the most common malignancies worldwide, gastric cancer contributes to cancer death with a high mortality rate partly responsible for its out-of-control progression as well as limited diagnosis. DNA methylation, one of the epigenetic events, plays an essential role in the carcinogenesis of many cancers, including gastric cancer. Long non-coding RNAs have emerged as the significant factors in the cancer progression functioned as the oncogene genes, the suppressor genes and regulators of signaling pathways over the decade. Intriguingly, increasing reports, recently, have claimed that abnormal DNA methylation regulates the expression of lncRNAs as tumor suppressor genes in gastric cancer and lncRNAs as regulators could exert the critical influence on tumor progression through acting on DNA methylation of other cancer-related genes. In this review, we summarized the DNA methylation-associated lncRNAs in gastric cancer which play a large impact on tumor progression, such as proliferation, invasion, metastasis and so on. Furthermore, the underlying molecular mechanism and signaling pathway might be developed as key points of gastric cancer range from diagnosis to prognosis and treatment in the future.